Corrosion inhibition of aluminium alloy AA6063-T5 by vanadates: Local surface chemical events elucidated by confocal Raman micro-spectroscopy. (March 2019) - Kharitonov, Dmitry S.; Sommertune, Jens; Örnek, Cem; Ryl, Jacek; Kurilo, Irina I.; Claesson, Per M.; Pan, Jinshan
Highlights: In-situ and ex-situ confocal Raman measurements revealed chemical states of vanadium compounds. The inhibition effect is mostly provided by a polymerized film with mixed V(V) and V(IV) species. Intermetallic particles in the alloy have a strong influence on the vanadate inhibition process. Deposition of polymerized vanadate compounds is mainly connected with micrometer-sized IMPs. The inhibition mechanism involves first reduction and then re-oxidation of the vanadium species. Abstract: Chemical interactions between aqueous vanadium species and aluminium alloy AA6063-T5 were investigated in vanadate-containing NaCl solutions. Confocal Raman and X-ray photoelectron spectroscopy experiments were utilised to gain insight into the mechanism of corrosion inhibition by vanadates. A greenish-grey coloured surface layer, consisting of V +4 and V +5 polymerized species, was seen to form on the alloy surface, especially on top of cathodic micrometre-sized IMPs, whereby suppressing oxygen reduction kinetics. The results suggest a two-step mechanism of corrosion inhibition in which V +5 species are first reduced to V +4 or V +3 species above cathodic IMPs, and then oxidized to mixed-valence V +5 /V +4 polymerized compounds.